The Impact of Digital Inbound Marketing on Admission Interest at Kebangsaan Republik Indonesia University: The Mediation Role of Campus Reputation and Brand Awareness - Muji Artiyani; Fansuri Munawar (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study analyzes the impact of inbound digital marketing on enrollment interest at Universitas Kebangsaan Republik Indonesia (UKRI), considering the mediating roles of university reputation and brand awareness. The findings indicate that inbound digital marketing significantly influences university reputation, brand awareness, and enrollment interest. However, the interactive communication aspect of inbound digital marketing needs improvement. University reputation and brand awareness were found to mediate the relationship between inbound digital marketing and enrollment interest. Although inbound digital marketing strategies are effective in increasing UKRI’s recognition, branding strategies need to be strengthened to position UKRI as the top choice for prospective students.